Performance Analysis of Smartphone-based Mobile Wi-Fi Hotspots Operating in a Congested Environment - Osama F; Abu-Sharkh Abu-Sharkh (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
In this work, we address the ubiquity of internet connections in smart cities by analyzing mobile Wi-Fi hotspots in terms of speed and energy efficiency in a congested Wi-Fi environment. We consider state-of-theart consumer smartphones in our work since they are the major devices in establishing mobile Wi-Fi hotspots nowadays. There are two main wireless connections in mobile Wi-Fi hotspots, the cellular connection and the Wi-Fi connection. It has been known that the speed of WiFi connections enormously supersedes the speed of cellular connections with the use of present technologies of each. In this work, we show that this well-known fact becomes controversial when establishing mobile Wi-Fi hotspots using smartphones in a nowadays typical congested Wi-Fi environment.